2003
DOI: 10.1046/j.1365-2648.2003.02781.x
|View full text |Cite
|
Sign up to set email alerts
|

Wandering behaviour in people with dementia

Abstract: Knowledge generated through research remains insufficient to explain fully why and when wandering occurs. Variability in how the phenomenon was defined and studied, and the small size of the samples made generalizability of findings difficult. Future research should incorporate a clearer definition of wandering; a specific targeted population with representative sample size; appropriate subject identification strategies; focussed interventions, and better control conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 63 publications
7
127
1
1
Order By: Relevance
“…Other attributes such as engagement with others and indoor gardening itself also could cause decrease in agitation. In contrast to the present results, several research groups concluded that the efficacy of physical activity on wandering was not robust (Lai and Arthur, 2003;Robinson et al, 2006). Since wandering is a critical attribute of agitation and study result is not fully convinced with low reliability of the tool, further study is called for.…”
Section: Gardening and Agitationcontrasting
confidence: 96%
“…Other attributes such as engagement with others and indoor gardening itself also could cause decrease in agitation. In contrast to the present results, several research groups concluded that the efficacy of physical activity on wandering was not robust (Lai and Arthur, 2003;Robinson et al, 2006). Since wandering is a critical attribute of agitation and study result is not fully convinced with low reliability of the tool, further study is called for.…”
Section: Gardening and Agitationcontrasting
confidence: 96%
“…105 This is corroborated by the findings of our small qualitative study. The focus of this systematic review was the prevention of wandering rather than the promotion of safe wandering or walking.…”
Section: Prevention Of Wandering Versus Promotion Of Safe Walkingsupporting
confidence: 86%
“…Management difficulties usually remain in nursing homes. Wandering is involved in most of the violent incidents in nursing homes (Shinoda-Tagawa et al, 2004) and no treatment has so far demonstrated unequivocal effectiveness (Lai and Arthur, 2003).…”
Section: Introductionmentioning
confidence: 99%